2010
DOI: 10.1111/j.1582-4934.2010.01186.x
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes accompanying cardiomyocyte in primary culture: two‐ and three‐dimensional culture environment

Abstract: Recently, the presence of telocytes was demonstrated in human and mammalian tissues and organs (digestive and extra-digestive organs, genitourinary organs, heart, placenta, lungs, pleura, striated muscle). Noteworthy, telocytes seem to play a significant role in the normal function and regeneration of myocardium. By cultures of telocytes in two- and three-dimensional environment we aimed to study the typical morphological features as well as functionality of telocytes, which will provide important support to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 31 publications
3
40
0
2
Order By: Relevance
“…Vimentin is an intermediate filament protein which is widely distributed in mesenchymal cells. It was also shown that some c-kit or CD34 immunopositive cells in engineered heart tissue have the morphology of telocytes, with a typical fusiform cell body and long moniliform telopodes, suggesting a possible role in the heart regeneration process, and a possible value as a tool for cardiac tissue engineering [25]. More importantly, we also found that cardiac TCs positively expressed stem cell markers nanog and sca-1.…”
Section: Discussionsupporting
confidence: 61%
“…Vimentin is an intermediate filament protein which is widely distributed in mesenchymal cells. It was also shown that some c-kit or CD34 immunopositive cells in engineered heart tissue have the morphology of telocytes, with a typical fusiform cell body and long moniliform telopodes, suggesting a possible role in the heart regeneration process, and a possible value as a tool for cardiac tissue engineering [25]. More importantly, we also found that cardiac TCs positively expressed stem cell markers nanog and sca-1.…”
Section: Discussionsupporting
confidence: 61%
“…We have previously isolated and cultured telocytes from neonatal rat cardiac tissue in two-and three-dimensional environments in vitro [27]. Our previous study confirmed that typical telocytes existed in primary culture in vitro and some c-kit, vimentin, or CD34-positive cells in EHTs exhibited the morphology of telocytes.…”
supporting
confidence: 57%
“…EHTs were constructed by combining freshly isolated cardiac cells from one-day-old Wistar rats with a collagen/Matrigel mixture as described previously [25,27]. In brief, 0.5 mL 2× H-DMEM (Invitrogen, Carlsbad, CA, USA) containing 20% fetal bovine serum (Invitrogen) was mixed with 0.5 mL liquid collagen type I and Matrigel (4 : 1, (v/v); Becton Dickinson Biosciences, San Jose, CA, USA).…”
Section: Eht Constructionmentioning
confidence: 99%
“…Telocytes accompanying cardiomyocyte in primary culture: two-and three-dimensional culture environment [Zhou et al, 2010a] Cardiac telocytes were decreased during myocardial infarction and their therapeutic effects for ischaemic heart in rat [Zhao et al, 2013] Intramyocardial transplantation of cardiac telocytes decreases myocardial infarction and improves post-infarcted cardiac function in rats [Zhao et al, 2014] Comparative analysis of telomerase activity in CD117(+) CD34(+) cardiac telocytes with bone mesenchymal stem cells, cardiac fibroblasts and cardiomyocytes [Li et al, 2015] Histological and immunohistochemical study of cardiac telocytes in a rat model of isoproterenol-induced myocardial infarction with a reference to the effect of grape seed extract [Nour et al, 2017] J Cell Mol Med…”
Section: The Markers Used To Identify Cardiac Tcs Can Be Challengedmentioning
confidence: 99%